Increasing Adolescents Knowledge of Sexually Transmitted Infections, Drugs and the Dangers of Smoking - Desi Apriani; Adelse Prima Mulya; Setiawan (Jurnal Kesehatan Cendikia Jenius, 2025)
Background: According to the results of the initial study at RW 15 Sukamentri Village, it was revealed that there was a lack of knowledge of adolescents related to sexually transmitted infections and drugs and was supported by the explanation of local cadres that reproductive health counseling activities for adolescents had never been held in the area. Based on this background, a nursing problem was found, namely a knowledge deficit in adolescents. Objective: To describe changes in knowledge of adolescents in RW 15 about sexually transmitted infections, drugs and the dangers of smoking. Methods: This study using descriptive methods approaches the nursing process with quantitative research design. Results: The average pre-test and post-test scores of respondents indicate an increase of 2.92 in the post-test results after receiving education. Conclusion: There is an increase in adolescent knowledge before and after health education about STIs, drugs and the dangers of smoking. Suggestion: Education programs for adolescents on STIs, drugs, and smoking could be a sustainable program in the community.